Mass- and power-related efficiency trade-offs and CO2 emissions of compact passenger cars. (10th January 2020) - Weiss, Martin; Irrgang, Lukas; Kiefer, Andreas T.; Roth, Josefine R.; Helmers, Eckard
Abstract: Passenger cars in Europe have become both heavier and more powerful over the past decades. This trend has increased vehicle utility but it might have also offset technical improvements in powertrain efficiency. Here, we analyze efficiency trade-offs and CO2 emissions for three popular compact cars in Germany. We find that mass, power, and front area of model variants has increased by 66%, 147%, and 22%, respectively between 1980 and 2018. In the same period, fuel consumption decreased 14% for gasoline models but it increased 9% for diesel models. However, if vehicle mass, power, and front area had remained at 1980 levels, technical efficiency improvements would have decreased the fuel consumption of gasoline and diesel models by 23% and 24%, respectively. The related efficiency trade-offs amount to 24 g CO2 /km or 13% of the current fuel consumption for gasoline models and 40 g CO2 /km or 25% of the current fuel consumption for diesel models. These findings suggest that about half of the technical efficiency improvements in gasoline models and all of the technical efficiency improvements in diesel models are offset through other vehicle attributes. By accounting for the observed efficiency trade-offs, climate policy could become more effective. Highlights: Mass and power of compact cars increased 66% and 147% between 1980 and 2018. Parts of technical efficiency improvements are offset by other vehicle attributes. If mass and power had remained as in 1980, CO2 emissions would decrease by 13% or 24 g/km for gasoline models and 25% or 40 g CO2 /km for diesel models.